Student and Teacher Coefficients in Large Ball Learning Through the Jigsaw Model at SMPN 1 Leles (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effect of the Jigsaw learning model on the correlation coefficient between students and teachers in teaching large ball games at SMPN 1 Leles. The method used is a quantitative method with a descriptive approach and a One Group Pretest–Posttest Design. The research sample consisted of 83 eighth-grade students obtained through purposive sampling based on the Slovin formula. The research instrument was a Likert scale questionnaire with 46 statements covering four aspects of assessment, namely cognitive, affective, psychomotor, and interaction. The questionnaire was administered at the pretest and posttest stages. The treatment was carried out through the application of the Jigsaw learning model during nine meetings on the subjects of basketball, volleyball, and soccer. Data analysis included descriptive analysis, Kolmogorov–Smirnov normality test, Levene's homogeneity test, and paired t-test. The results showed an increase in scores from the pretest to the posttest with an average difference of 8.597 and a significance value of 0.000 (p < 0.05), indicating a significant difference after the Jigsaw model was applied. Normality and homogeneity tests also showed that the data were normally distributed and had homogeneous variance. Overall, this study concluded that the Jigsaw learning model had a significant effect on increasing the correlation coefficient between students and teachers. This model was able to create a more active, collaborative, and communicative learning atmosphere, thereby supporting the improvement of the effectiveness of large ball game learning.